2019
DOI: 10.33546/bnj.913
|View full text |Cite
|
Sign up to set email alerts
|

Application of Health Promotion Model for Better Self-Care Behavior in Patients With Diabetes Mellitus

Abstract: Background: Diabetes mellitus (DM) is a major health problem in the world. DM patients should be able to perform self-care behavior. Diabetic self-care behavior is an effective strategy for controlling diabetes.Objective: The purpose of this study was to examine a health promotion model in patients with type 2 diabetes mellitus.Methods: A cross-sectional design was used, which involved 177 patients with type 2 diabetes from primary health care in Denpasar Bali Indonesia with a stratified random sampling. Indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
(22 reference statements)
0
3
0
3
Order By: Relevance
“…tarafından yapılan bir diğer çalışmada ise diyabetli bireylerde sağlığı geliştirme modelinin öz bakım davranışları üzerindeki etkisi incelenmiştir ve çalışmanın sonucunda diyabet öz bakım davranışı sosyoekonomik durum, eğitim düzeyi, hastalık algısı ve aile desteğinden etkilenmektedir. 46 Bu nedenle hemşirelerin Tip 2 diyabetli hastaların öz bakım davranışlarını artırmak için sağlığı geliştirme modeli yaklaşımını uygulamaları önerilmiştir. İstek ve Karakurt'un diyabetli bireylerde öz bakım yönetimi çalışmasında ise diyabet tanısı konan bir hastada hastalığın yönetimi ve tedavinin başarısı için hastaya diyabet nedenleri, tedavi seçenekleri, beslenme ve egzersizin önemi, öz bakım, kan glikoz düzeylerinin takibi, tedavi uyumu, beklenmeyen durumlarla başa çıkma, komplikasyonları tanıma ve önleme gibi konularda eğitim verilmesinin önemi paylaşılmıştır.…”
Section: Discussionunclassified
“…tarafından yapılan bir diğer çalışmada ise diyabetli bireylerde sağlığı geliştirme modelinin öz bakım davranışları üzerindeki etkisi incelenmiştir ve çalışmanın sonucunda diyabet öz bakım davranışı sosyoekonomik durum, eğitim düzeyi, hastalık algısı ve aile desteğinden etkilenmektedir. 46 Bu nedenle hemşirelerin Tip 2 diyabetli hastaların öz bakım davranışlarını artırmak için sağlığı geliştirme modeli yaklaşımını uygulamaları önerilmiştir. İstek ve Karakurt'un diyabetli bireylerde öz bakım yönetimi çalışmasında ise diyabet tanısı konan bir hastada hastalığın yönetimi ve tedavinin başarısı için hastaya diyabet nedenleri, tedavi seçenekleri, beslenme ve egzersizin önemi, öz bakım, kan glikoz düzeylerinin takibi, tedavi uyumu, beklenmeyen durumlarla başa çıkma, komplikasyonları tanıma ve önleme gibi konularda eğitim verilmesinin önemi paylaşılmıştır.…”
Section: Discussionunclassified
“…According to Bandura's theory, 17 when self-efficacy increases, the elderly are more likely to engage in health promotion self-care behaviors, thereby improving their quality of life and well-being. 25,26 Reisi, et al, 27 found that individuals with higher self-efficacy were more motivated to improve their self-care practices. Noticeably, the study results indicated that the elderly with multimorbidity receiving the intervention showed significantly improved self-care practices in healthy eating, physical activity, exercise, stress management, and medication.…”
Section: Discussionmentioning
confidence: 99%
“…Self efficacy mengembangkan kepercayaan diri dalam kemampuan individu untuk melakukan perilaku dan untuk mengatasi hambatan untuk mencapai tujuan tersebut. Hasil yang diinginkan adalah keyakinan seseorang bahwa mereka akan mencapai hasil kesehatan positif yang dihasilkan dari perilaku yang spesifik (13) . Self efficacy berhubungan dengan motivasi individu dan keyakinan tentang kemampuan mereka dan semua hal tersebut adalah syarat yang paling penting bagi perubahan perilaku (13,14) .…”
Section: Pembahasanunclassified
“…Hasil yang diinginkan adalah keyakinan seseorang bahwa mereka akan mencapai hasil kesehatan positif yang dihasilkan dari perilaku yang spesifik (13) . Self efficacy berhubungan dengan motivasi individu dan keyakinan tentang kemampuan mereka dan semua hal tersebut adalah syarat yang paling penting bagi perubahan perilaku (13,14) . Pada penelitian ini ditemukan keyakinan diri lansia dengan hipertensi dalam kategori baik.…”
Section: Pembahasanunclassified